PERLINDUNGAN HUKUM LELANG EKSEKUSI HAK TANGGUNGAN - Asuan, Asuan (Faculty of Law, University of Palembang, 2021)
Parate Executie or direct execution, namely the execution of mortgage rights which is carried out by selling the object of the mortgage right by the holder of the first mortgage on his own power through a public auction and taking the payment of the debt from the sale proceeds. Protection of mortgage auction has actually been carried out in a preventive manner by the State Wealth and Auction Service Office (KPKNL) because prior to the auction, KPKNL notifies the auction participants regarding the documents, conditions and conditions of the object to be auctioned in truth and as it is as well as the consequences and risks that may arise from the auction object. Regarding repressive protection, namely efforts to obtain legal protection through judicial bodies and obstacles to implementation, there is no agreement on the price of the object being auctioned.